Autoclave reactor synthesis of upconversion nanoparticles, unreported variables, and safety considerations - Rebecca McGonigle; Jodie Glasgow; Catriona Houston; Iain Cameron; Christian Homann; Dominic J. Black; Robert Pal; Lewis E. MacKenzie (Communications Chemistry)
Abstract Autoclave reactors are widely used across chemical and biological sciences, including for the synthesis of upconversion nanoparticles (UCNPs) and other nanomaterials. Yet, the details of how autoclave reactors are used in such synthesis are rarely reported in the literature, leaving several key synthesis variables widely unreported and thereby hampering experimental reproducibility. In this perspective, we discuss the safety considerations of autoclave reactors and note that autoclaves should only be used if they are (a) purchased from reputable suppliers/manufacturers and (b) have been certified compliant with relevant safety standards. Ultimately, using unsuitable autoclave equipment can pose a severe physical hazard and may breach legal safety requirements. In addition, we highlight several parameters in autoclave synthesis that should be reported as standard to maximise the reproducibility of autoclave synthesis experiments across materials and chemistry research. We encourage users of autoclave synthesis vessels to: (1) adopt high-safety autoclaves and (2) report the many experimental variables involved to enhance experimental reproducibility.